Karakteristik Variasi Lateral Tilt Angle pada Friction Stir Welding Material High Density Polyethylene Terhadap Kekuatan Tarik dan Bending - Azara, Salsa Bila; Ramadhani, Risky; Budi Darsono, Febri Budi; Bahatmaka, Aldias; Kriswanto, Kriswanto; Firmansyah, Hendrix Noviyanto (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2025)
Friction Stir Welding (FSW) is a solid-state joining method suitable for thermoplastics like HDPE, which has lighter and more flexible properties. This study aims to examine the tensile and bending strength of HDPE joints influenced by parameters such as TRS 930 rpm, a feed rate of 20mm/min, and variations in the Lateral Tilt Angle (LTA) of 0°, 0,5°, 1°, and 1,5°, where the tool's position is sideways relative to the tool's movement direction as the main variable. Resulting in maximum tensile strength (UTS) values of 3,15 MPa, 16,0 MPa, 16,9 MPa, and 8,59 MPa. LTA 1° produced the highest UTS, while LTA 0° produced the lowest UTS because the heat input was not sufficient to perfectly bond the welding material. The bending strength values produced were 4,25 MPa, 14,3 MPa, 4,17 MPa, and 28,8 MPa. The highest stress is found at a 1,5° variation and the lowest at a 1° variation, due to uneven heat distribution during the FSW process. Therefore, choosing the right TLA during the FSW process is key to achieving HDPE joints with good mechanical strength.